Modeling green technological imports in the Belt and Road economies - Dan Tan; Ziqiong Xiao; Xiantai Hong (Humanities & Social Sciences Communications)
Abstract This study applied the Continuously Updated Bias-Corrected technique to examine the importation of green technologies—such as smart grids, electric vehicles, solar panels, wind turbines, and hydraulic turbines—into 30 countries involved in the Belt and Road Initiative (BRI) between 2010 and 2020. The findings reveal that economic uncertainty, or risk, significantly restricts green technology imports within BRI countries, reducing imports by 0.54% and indicating a substantial barrier caused by financial market instability and cautious spending patterns. Population size is associated with a 0.25% decrease in green technology imports, likely due to resource strains and policy coordination challenges, while larger economic size also negatively influences imports by 0.05%, reflecting reliance on non-green technologies. In contrast, financial development positively influences green technology imports, with a 1% improvement in financial development driving a 0.37% increase in imports. These findings offer valuable policy insights for BRI economies. Promoting environmentally sustainable growth by encouraging green technology adoption, advancing smart city initiatives, improving waste management, and strengthening financial markets can support sustainable development and enhance green technology imports. Additionally, reinforcing regulatory frameworks and promoting sustainable investment practices are crucial steps to attract investments in green technology and infrastructure aligned with sustainability goals.